Kiai Kampung as Normative Brokers: Negotiating Inheritance Legal Pluralism in Rural Java - Arif, Miftakhul; Ali, Sapri; Bastomi, Ahmad (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2026)
This study examines how Kiai Kampung in Jombang negotiate competiting legal systems and explores the implications for legal pluralism theory. Using  a qualitative socio-legal approach, the research draws on observations, in-depth interviews with seven Kiai Kampung, village officials, and local residents, as well as document analysis. The finding shows that Kiai Kampung act as consultants, educators, advisors, and mediators through five locally grounded strategies rooted in Javanese Islamic-values. The study identifies three variants of Kiai Kampung: textualist, culturalist, and moderate, each representing different approaches to reconciling faraid and customary inheritance practices. Unlike previous studies emphasizing legal contestation, this research introduces the concept of normative brokerage, referring to the ability of local actors to select, validate, and operationalize forms of ‘urf to transform normative conflict into complementarity. The study also extends structural-functionalist theory by demonstrating that social equilibrium in plural legal system depends on local actors capable of bridging competing normative frameworks.